(untitled) (Música Hodie, 2019)
This article examined into three Chinese composers’ compositional method based on the ancient Chinese philosophy I Ching. Transcoding the 64 hexagrams of the I Ching in the piano solo works of Chou Wen Chung, Zhao Xiao Sheng and Chung Yiu Kwong display new representative of Chinese New Music. The analysis shows Chou and Chung’s creations that emphasize the use of the 64 hexagrams within a Westernized context, while Zhao brought out a new and individual compositional method based on the Chinese ancient philosophy that shows a complete departure from the West.